Fabrication of a cell irradiation technique by alpha-particles using allyl diglycol carbonate (ADC) detector and micro-capillary tubes - Runas Yakup Sula; Asaad Hamid Ismail (Journal of the Pakistan Medical Association, 2024)
Objective: To study the impact of micro-alpha irradiation collimator with a specific design to irradiate specific normal or up-normal cells using capillary tubes and nuclear track detector type CR-39. Method: The in vitro experimental study was conducted at radiobiology Lab, of the Physics department, Salahaddin University, Erbil, Iraq from February to April 2022. Several alpha irradiation collimators were calibrated using allyl diglycol carbonate to fabricate a suitable blood cell irradiation technique. Time of irradiation and alpha particle energy were calibrated. Healthy blood samples of Albino rats and cancer blood samples were used to assess the applicability of the fabricated cell irradiation technique. The Rats were divided into intervention and control groups. Data was analysed using SPSS software version 28. Results: Of the 15 healthy, male Albino rats having a mean weight of 230±12g each, there were 12(80%) in the intervention group and 3(20%) in the control group. Microcapillary tubes with suitable diameters had high stability for deposition of a sufficient density of alpha particles on the surface of allyl diglycol carbonate and blood samples. The optimum time of irradiation that had a significant (p<0.05) effect was 20 sec corresponding to alpha energy 4.5MeV. Conclusion: Low irradiation time had significant impact of alpha particles on the average percentage of lymphocyte and neutrophil cells. Key Words: Neutrophils, Neoplasms, Radiobiology, Carbonates, Lymphocytes